APPLICATION OF LEAN LAYOUT PLANNING TO REDUCE WASTE IN A SLIPPERS MANUFACTURING: A CASE STUDY - Faishal, M.; Mohamad, E.; Pratama, M.A.; Abdul Rahman, A.A.; Adiyanto, O. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
Lean principles encourage every company to reduce waste in all aspects to achieve optimal productivity. One application area in the domain is layout planning, which can help reduce interdepartmental distance and enhance throughput. This research is based on Azka Pratama, which is a small and medium-sized enterprise (SME) producing sponge slippers in Yogyakarta, Indonesia. The company faces material handling challenges between departments leading to higher production time and low throughput. This study intends to improve the layout of the facility so as material handling time may be reduced. In the context of this research, facility layout redesigning employs the activity relationship chart (ARC) and computerized relative allocation facilities technique (CRAFT) methods after which, simulations were used to analyze the proposed layouts. The results indicate that the CRAFT technique reduced the distance by 53.76% and material handling time by 37.13%, leading to a throughput enhancement of 2.39%. In comparison, the ARC method leads to 34.29% and 25.52% reduction in distance and material handling time, respectively, thereby leading a throughput increase of 3.75%. For implementation, the new layout resulting from CRAFT methods is recommended because the renovation cost is cheaper than ARC methods with the result is closer to ARC.